2017
DOI: 10.1007/s00344-017-9692-8
|View full text |Cite|
|
Sign up to set email alerts
|

Ethylene Controls Adventitious Root Initiation Sites in Arabidopsis Hypocotyls Independently of Strigolactones

Abstract: mutants together with GR24 (strigolactone agonist) treatments. Importantly, we conducted a detailed mapping of adventitious root initiation along the hypocotyl and measured ethylene production in strigolactone mutants. ACC treatments resulted in a slight increase in adventitious root formation at low doses and a decrease at higher doses, in both wild-type and strigolactone mutants. Furthermore, the distribution of adventitious roots dramatically changed to the top third of the hypocotyl in a dose-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…In prolonged darkness, plants start to senesce, a process that is promoted by ethylene (Johnson and Ecker, 1998;Wang et al, 2002). Ethylene accumulation during an extended dark period has been shown previously for rice and Arabidopsis (Fukao et al, 2012;Rasmussen et al, 2017). In this study, we show that inhibition of ethylene signaling abolishes dark-induced AR emergence, supporting the conclusion that AR growth is mediated by ethylene both in the dark and during submergence.…”
supporting
confidence: 74%
“…In prolonged darkness, plants start to senesce, a process that is promoted by ethylene (Johnson and Ecker, 1998;Wang et al, 2002). Ethylene accumulation during an extended dark period has been shown previously for rice and Arabidopsis (Fukao et al, 2012;Rasmussen et al, 2017). In this study, we show that inhibition of ethylene signaling abolishes dark-induced AR emergence, supporting the conclusion that AR growth is mediated by ethylene both in the dark and during submergence.…”
supporting
confidence: 74%
“…Both ethylene overproducing 2‐1 and eto3‐1 mutants, and constitutive triple response1‐1 mutants, which have constitutive ET signaling, produced more ARs, while ethylene insensitive2‐1 and ein3‐1 mutants produced fewer ARs, than wild‐type controls. To the same end, Rasmussen et al () showed that at very low concentration (0.01 μM) ACC induced slightly higher AR densities, but higher concentrations (0.1–1 μM) had no significant effect. These results clearly indicate that ET biosynthesis and signaling promote AR formation.…”
Section: Ethylene: the Gas That Mattersmentioning
confidence: 94%
“…SLs apparently promote AR formation in rice via the D4‐dependent pathway, probably by modulating IAA transport (Sun et al ). However, they seem to inhibit AR formation in tomato ( S. lycopersicum ), pea ( Pisum sativum ) and Arabidopsis (Kohlen et al , Rasmussen et al , ). Kohlen et al () found that AR numbers were significantly increased in CAROTENOID CLEAVAGE DIOXYGENASE 8 ( SlCCD8 ) RNAi transgenic lines, suggesting that SL‐mediated AR formation is species‐dependent.…”
Section: Strigolactones: the Newcomers To The Clubmentioning
confidence: 99%
“…In A. thaliana it acts as a negative regulator of AR formation, similar to SLs. While A. thaliana SL mutants are sensitive to treatment with the ethylene precursor 1-aminocyclopropane-1-carboxylic acid, mutants in ethylene biosynthesis and signalling are sensitive to racGR24 treatment [ 60 ]. When both hormones were applied the response was stronger in comparison to the single treatments, an indication that both phytohormones act independently in the repression of AR development [ 60 ].…”
Section: How Sls Influence On Root Developmentmentioning
confidence: 99%